Examination of the functions and mechanism of KCP in mediating paclitaxel resistance in cervical squamous carcinoma cells - He, Yue; Xu, Jian-Qing; Zhang, Jing-Jing; Liu, Zhen-You; Ji, Chen; Liu, Yang; Wang, Yun-Fan; Wang, Ming; Wu, Yu-Mei; Wang, Yan (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the mechanism of Kielin/chordin-like protein (KCP) in the resistance of cervical cancer cells to paclitaxel.MethodA cervical squamous carcinoma cell line (SiHa) with KCP knockout was constructed and treated with paclitaxel. Key cell functions were assessed by colony formation assay, measurement of cell proliferation by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, and FACS-based detection of apoptosis. The downstream mechanism of KCP-mediated resistance to paclitaxel was then examined using human gene chip detection and IPA bioinformatics analysis, and qPCR analysis was used to validate its downstream genes.Results①Functional studies of SiHa cells showed that KCP knockout (sgRNA) inhibited colony formation and proliferation of SiHa cells in the presence of paclitaxel (p<0.05). ②Using a whole human genome microarray, a total of 491 differentially expressed genes were identified in KCP knockout versus the NC SiHa cells. IPA-based bioinformatics analysis of upstream regulators showed that SPI1 was strongly activated and that SPI1 inhibited CCND1 and activated PML and CEBPA, which is consistent with results from gene chip analysis showing CCND1, PML, and CEBPA expression after KCP knockout. ③A total of 30 differentially expressed genes associated with tumor cell proliferation were identified by gene microarray and IPA analyses. The changes in the aforementioned genes after KCP knockout were verified by qPCR, and SERPINB3 and CEBPA expression were significantly lower and higher, respectively, compared to in the control group.ConclusionKCP increased resistance of cervical cancer to paclitaxel by enhancing cell proliferation and colony formation. We observed that KCP could act positively on the downstream gene SERPINB3 and negatively on the downstream gene CEBPA to affect the resistance of cervical carcinoma cells to paclitaxel.